PM10 and Pseudomonas aeruginosa: effects on corneal epithelium - Somayajulu, Mallika; McClellan, Sharon A.; Muhammed, Farooq; Wright, Robert; Hazlett, Linda D. (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose In vivo data indicate that mouse corneas exposed to PM10 showed early perforation and thinning after infection with Pseudomonas aeruginosa. To understand the mechanisms underlying this finding, we tested the effects of PM10 and the mitochondria targeted anti-oxidant SKQ1 in immortalized human corneal epithelial cells (HCET) that were challenged with Pseudomonas aeruginosa strain 19660. Methods Mouse corneas were infected with strain 19660 after a 2 week whole-body exposure to PM10 or control air and assessed by clinical scores, slit lamp photography and western blot. HCET were exposed to 100μg/ml PM10 for 24h before challenge with strain 19660 (MOI 20). A subset of cells were pre-treated with 50nM SKQ1 for 1h before PM10 exposure. Phase contrast microscopy was used to study cell morphology, cell viability was measured by an MTT assay, and ROS by DCFH-DA. Levels of pro-inflammatory markers and anti-oxidant enzymes were evaluated by RT-PCR, western blot and ELISA. Reduced glutathione (GSH) and malondialdehyde (MDA) levels were evaluated by assay kits. Results In vivo, whole body exposure to PM10 vs. control air exposed mouse corneas showed early perforation and/or corneal thinning at 3 days post infection, accompanied by increased TNF-α and decreased SOD2 protein levels. In vitro, PM10 induced a dose dependent reduction in cell viability of HCET and significantly increased mRNA levels of pro-inflammatory molecules compared to control. Exposure to PM10 before bacterial challenge further amplified the reduction in cell viability and GSH levels. Furthermore, PM10 exposure also exacerbated the increase in MDA and ROS levels and phase contrast microscopy revealed more rounded cells after strain 19660 challenge. PM10 exposure also further increased the mRNA and protein levels of pro-inflammatory molecules, while anti-inflammatory IL-10 was decreased. SKQ1 reversed the rounded cell morphology observed by phase contrast microscopy, increased levels of MDA, ROS and pro-inflammatory molecules, and restored IL-10. Conclusions PM10 induces decreased cell viability, oxidative stress and inflammation in HCET and has an additive effect upon bacterial challenge. SKQ1 protects against oxidative stress and inflammation induced by PM10 after bacterial challenge by reversing these effects. The findings provide insight into mechanisms underlying early perforation and thinning observed in infected corneas of PM10 exposed mice.